Penapisan dan Edukasi Tuberkulosis Paru pada Warga Desa Titi Akar Kecamatan Rupat Utara - Nori Purnama; Dewi Anggraini; Sri Indah Indriani (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2024)
ABSTRACT Tuberculosis (TB) is a contagious chronic lung disease caused by infection from the Mycobacterium tuberculosis (M.Tb) group of bacteria, which consists of eight different and interrelated species. Patients with pulmonary TB in 2021 globally amounted to 10.6 million people in the world, this figure increased by 4.5% compared to 2020, which was 10.1 million people. The highest number of TB cases in Southeast Asia is occupied by India, Indonesia, and China, followed by Africa (23%) and the Western Pacific (18%). Riau still has areas that are difficult to reach, one of which is Rupat Island which is one of the islands included in the Bengkalis Regency area. The lack of knowledge about tuberculosis to the people of Indonesia, especially in rural areas such as Titi Akar Village, North Rupat District, so health workers are obliged to provide education about tuberculosis disease and how to detect pulmonary TB disease early. Community service activities and lung health checks for residents of Titi Akar Village, North Rupat District, Bengkalis Regency, Riau Province are very useful and important for these villagers. This activity is expected to increase knowledge and know the number of patients suffering from Tuberculosis disease based on the results of doctor's examination and Molecular Rapid Test examination. Keyword : Tuberculosis, Molecular Rapid Tes, North Rupat